The dragon king /3 - Johnson-Shelton, Nils (Johnson-Shelton, Nils. Otherworld chronicles, 2014)
"Artie Kingfisher's quest to claim his throne as King Arthur reborn approaches its end as he reaches the mythical isle of Avalon, sets off in search of the Holy Grail, and prepares to face off in battle agains the wizard Merlin"--Provided by publisher.